TEACHING VISUALLY IMPAIRED PEOPLE AND STUDENTS WITH DISABILITIES IN UNIVERSITIES - Eshmuratov, Umidjon (Журнал иностранных языков и лингвистики, 2021)
Its vital to note that teaching in time of technological progress and human development with the ways of easy accessible devices progressing tremendously, hence arises a question, are the Universities ready to accept a challenge which obviously teachers will face while teaching visually impaired students? Does they have all necessary tools, conditions, atmosphere, skills and definitely the methods? The main areas that have been taken into account in this research are, visual impairment and its impact on learning, adaptive teaching methods for students with visual impairments, using kinesthetic, auditory and visual modalities in teaching.